The Making of a New Rural Order in South China : n - McDermott, Joseph P. (Cambridge : Cambridge University Press, 2013)
Among the large caches of private documents discovered and collected in China, few rival the Huizhou sources for the insight they provide into Chinese local society and economy over the past millennium. Having spent decades researching these exceptionally rich sources, Joseph P. McDermott presents in two volumes his findings about the major social and economic changes in this important prefecture of south China from around 900 to 1700. In this first volume, we learn about village settlement, competition among village religious institutions, premodern agricultural production, the management of land and lineage, the rise of the lineage as the dominant institution, and its members' application of commercial practices to local forestry operations. This landmark study of religious life and economic activity, of lineage and land, and of rural residents and urban commercial practices provides a compelling new framework for understanding a distinctive path of economic and social development for premodern China and beyond.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).